Lean from the Trenches: Managing Large-Scale Projects with Kanban - Kniberg, Henrik (Pragmatic Bookshelf, 2011)
You know the Agile and Lean development buzzwords, you've read the boo ks. But when systems need a serious overhaul, you need to see how it w orks in real life, with real situations and people. Lean from the Tren ches is all about actual practice. Every key point is illustrated with a photo or diagram, and anecdotes bring you inside the project as you discover why and how one organization modernized its workplace in rec ord time.Lean from the Trenches is all about actual practice.Find out how the Swedish police combined XP, Scrum, and Kanban in a 60-person p roject. From start to finish, you'll see how to deliver a successful p roduct using Lean principles. We start with an organization in despera te need of a new way of doing things and finish with a group of sixty, all working in sync to develop a scalable, complex system. You'll wal k through the project step by step, from customer engagement, to the d aily "cocktail party," version control, bug tracking, and release. In this honest look at what works–and what doesn't–you'll find out how to :Make quality everyone's business, not just the testers.Keep everyone moving in the same direction without micromanagement.Use simple and po werful metrics to aid in planning and process improvement.Balance betw een low-level feature focus and high-level system focus.You'll be read y to jump into the trenches and streamline your own development proces s.